Necrosis and abscess in the posterior thigh due to loxosceles bite - Caramori, Jeanine Eggers (2008)
Case of a 62-year-old woman presenting with erythematous lesion measuring 7 cm in the posterior thigh, with edema, singns of necrosis and yellow-greenish purulent matter in the center, accompanied by severe pain. The lesion was due to the bite of a spider of the genus loxosceles. Based on these clinical evidences the the wound was debrided and the purulent discharge was drained with complete excision of the area and total remission of symptoms.